Cultural Aspects of Translation and its Problematics in Brothers Grimm Fairy-tales - Kumar, Bikram (Journal of Advanced Research in English & Education, 2021)
19th century was largely marked by Grimm’s fairy tales leading to the demand of translations for children across cultures. Brothers Grimm’s work played a vital role in overall development of German language, history and nation building. The focus of this article primarily is to discern the relevance of German Linguist and Folklorist Jacob Grimm and Wilhelm Grimm’s Kinder- und Hausmärchen and its translation. Unfortunately, in the course of time and with the different translations of Grimm texts, the relevance and essence are diverging and now only names seem to be left living. The brothers Grimm certainly had some goals behind the collection of Fairy Tales; and it is well established among the scholars that the collections of fairy tales helped creating new culture and shaping history of Germany as a nation. Not to forget that they helped enormously in the development and standardization of Germanlanguage ( Hochdeutsch ).  How to cite this article: Kumar B. Cultural Aspects of Translation and its Problematic in Brothers Grimm Fairy-tales. J Adv Res Eng & Edu 2021; 6(2): 1-4. DOI: https://doi.org/10.24321/2456.4370.202101